KONSEP KEADILAN DAN KESETARAAN GENDER TENTANG PEMBAGIAN HARTA WARIS DALAM PERSFEKTIF HUKUM ISLAM - Nashirun, Kurniati, Marilang (FAKULTAS HUKUM UM PAREPARE, 2022)
One of the most complicated issues relates to the distribution of inheritance from parents to their children or people who have died to those who are entitled to receive it and this often creates problems for family members. It is customary in society that a problem arises usually from the practice of dividing inheritance because two parties usually feel that there is no justice in the distribution of inheritance. Due to the change in roles between women and men, this is a gender issue in society, the demands that are expected by women must be in accordance with the role in the family, so that the distribution of inheritance can also accommodate the needs of the community who provide justice for women in the future. recently. In this study, the concept of justice and gender equality in the distribution of inheritance from the perspective of Islamic law is presented. The real meaning of justice in Islamic inheritance is not measured by the level of equality between heirs, but what is the basis of justice in Islamic inheritance is the size of the role or burden or responsibility given to them. The obligation of a man is to provide for his family members, so it is proper for a man to be twice as big as a woman. So there is no discrimination against women seen from the magnitude of the obligations carried out by a man. So the comparison of two to one does not constitute a form of oppression against women, instead it emphasizes that women also have the same rights in the distribution of inheritance, namely equally receiving inheritance and there is no gender in Islam, both men and women.